Dependence of terms of Iris hybrida hort. flowering on a temperature factor in the conditions of the steppe zone of Ukraine - Chypylyak, T. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Iris hybrida hort. is one of the most common flower cultures in the world and is widely used in the design of spring landscape compositions. Researchers have confirmed the wide adaptive capabilities of representatives of the genus Iris L. under various climatic conditions, but a very limited number of varieties has been found in the green plantations of Kryviy Rih (steppe zone of Ukraine). It seems important to study the characteristics of the development of irises in our climatic conditions, taking into account the fact that over the past 30 years the average annual air temperature in Kryvyi Rih has increased by 2°C. The purpose of the research is to analyze the influence of the temperature factor on the generative development of Iris hybrida hort. during climatic changes in the steppe area of Ukraine. The objects of research were varieties of irises, which differed in terms of the beginning of flowering: early-flowering (beginning of flowering in early May), middle-flowering (second decade of May) and late-flowering (third decade of May). Passing of the phases of generative development (beginning of flowering, mass flowering and its total duration) for the last 17 years (2002–2018) has been analyzed. It was revealed that in conditions of the Kryviy Rih Botanical Garden, in 2002–2018, early-flowering Iris hybrida hort. began to flower on the average on 68th day of spring (on May 7), middle-flowering – on 74th day (on May 13), and late-flowering – on 80th day of spring (on May 19). In our climatic conditions, Iris hybrida hort. began flowering at various temperature indices: average daily temperature of air – from 9°C to 24°C, at the accumulation of the sum of effective temperatures above 5°С – for the early-flowering irises within 170-340°С, for the middle-flowering within 260 to 440°С, for the late-flowering within 310 to 500°С. Calculations of the regression dependence of the beginning of the flowering phase on the sum of effective air temperatures above 5°С showed the presence of a direct relationship of moderate degree (correlation coefficient is 0.48). A group of middle-flowering varieties was rather conditional and at the changes of weather, such varieties may correspond to early-flowering or late-flowering plants by the terms of flowering. The terms of the beginning of flowering of the middle-flowering and late-flowering varieties did not significantly change during 2002–2018, whereas early-flowering in the last five years began flowering 5–7 days earlier (April 28 – May 5) and reduced the duration of the decorative effect by 1.5 times. The middle-flowering varieties while reducing the total duration of flowering (by 1.2 times) for the last 17 years began to bloom massively at the end of the second decade of May invariably. The late-flowering varieties for the period of research do not show significant differences in the generative development, duration of flowering does not change in this group.